Unveiling The Ergo-Iconic Brand Strategy: A Qualitative Exploration of An Sem-Amos Model for Socially Responsible Investment - Andriyansah Andriyansah; Fatia Fatimah (AIBPM Publisher, 2025)
The transition toward Socially Responsible Investment (SRI) in emerging markets requires more than regulatory ESG compliance. Despite the growing body of SRI literature, a theoretical gap persists regarding how non-financial brand heuristics influence investor capital allocation under conditions of information opacity. This study introduces the novel concept of